Role models in the media: a content analysis of preschool television programs in the U.S. Issue 3 (2nd July 2020) - Hamlen, Karla R.; Imbesi, Krista J.
ABSTRACT: Preschool children in the United States spend a great deal of time watching television. The content and characters represented on preschool television programs play a role in children's learning and behavior. The purpose of this content analysis was to investigate role models in television programs targeted toward preschool children, with research questions focusing on gender and race/ethnicity of lead characters, content themes, leadership roles, comparison of public and private networks, and demographics of program creators. One hundred thirty-six programs from public television, cable channels, and private networks/streaming services were analyzed using descriptive statistics and Chi-Square tests of independence. Findings revealed more male than female lead characters and more white, non-Hispanic characters than underrepresented races/ethnicities. Males were more likely than females to be lead characters on programs about STEM and problem-solving. There was a greater proportion of males portrayed as group leaders, corresponding to the greater proportion of male lead characters. Creators of preschool television programs are primarily white and are more often male. Recommendations for improvement of diversity and equality are made.